Rice production in Chitwan district of Nepal: An analysis from economic and environmental perspectives - Sapkota, Bidya Kiran; Subedi, Ananta Prakash; Tripathi, Kalyani Mishra; Dhakal, Shiva Chandra; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2021)
Rice (Oryza sativa L.) is the major staple food in the Nepalese context. Chitwan district of Nepal was purposively selected to analyze the rice production from the socio-economic and environmental perspective. A total of 100 rice growing farmers, 50 organic and 50 inorganic were selected as the sample for the purpose of the study using the simple random method of sampling. Primary data were collected through a pre-tested semi-structure interview schedule and key informant interviews; secondary data were collected reviewing related publications. Descriptive statistics, multiple regression and chi-square test were used for data analysis. The multiple regression revealed that the four explanatory variables included in the model: age of the household head, primary occupation of the household head, number of family members involved in agriculture and subsidy in inputs for rice farming were found to have positive and statistically significant effect on rice yield (P<0.01). Moreover, chi-square test revealed that the farming practices that contributes to climate change mitigation such as: minimum tillage practice (P<0.05), crop diversification (P<0.01), green manuring (P<0.01), agro forestry practice (P<0.05), incorporating crop residues (P<0.1), weed management practice (P<0.01) and pest management practice (P<0.01)were found to be well adopted by the organic rice farmers, in contrast, the farming practices of inorganic rice farmers were statistically and significantly different in this respect. Government should make such policy that could grave the attention of the Nepalese people towards organic agriculture; moreover, encouraging them to make it their primary occupation.